2018
DOI: 10.1038/s41375-018-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

The cell fate determinant Scribble is required for maintenance of hematopoietic stem cell function

Abstract: Cell fate determinants influence self-renewal potential of hematopoietic stem cells. Scribble and Llgl1 belong to the Scribble polarity complex and reveal tumor-suppressor function in drosophila. In hematopoietic cells, genetic inactivation of Llgl1 leads to expansion of the stem cell pool and increases self-renewal capacity without conferring malignant transformation. Here we show that genetic inactivation of its putative complex partner Scribble results in functional impairment of hematopoietic stem cells (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Asymmetric cell division and subsequent asymmetric distribu-tion of fate determinants (some shared with fly neuroblasts) both require Scribble function, shaping the relative numbers of different T cell subsets (Pham et al, 2015). Conditional knockout suggests that Scribble plays a similar role in hematopoietic stem cell maintenance (Mohr et al, 2018). In contrast, it does not play a similar role in the erythrocyte lineage (Wölwer et al, 2017).…”
Section: Polarizing Mitosis: Roles For Scribble In Asymmetric Cell Divisionmentioning
confidence: 99%
“…Asymmetric cell division and subsequent asymmetric distribu-tion of fate determinants (some shared with fly neuroblasts) both require Scribble function, shaping the relative numbers of different T cell subsets (Pham et al, 2015). Conditional knockout suggests that Scribble plays a similar role in hematopoietic stem cell maintenance (Mohr et al, 2018). In contrast, it does not play a similar role in the erythrocyte lineage (Wölwer et al, 2017).…”
Section: Polarizing Mitosis: Roles For Scribble In Asymmetric Cell Divisionmentioning
confidence: 99%
“…The DNMT3A mutations were previously detected using the MiniSeq System (TruSight Myeloid Sequencing Panel, VariantStudio Software 3.0, Illumina, San Diego, USA). For analysis, murine bone marrow cells were isolated from the femurs as previously described [12]. Bone marrow samples were then assessed for clonal selection of the known DNMT3A mutations by pyrosequencing, according to standard protocols.…”
Section: Patient-derived Xenograft (Pdx) Modelmentioning
confidence: 99%
“…[16][17][18] We and others have shown that HSC maintenance and activity are influenced by several known intrinsic effectors of polarity establishment and asymmetrically associated cell fate determinants. [19][20][21][22] However, not all such factors seem to have the same mechanism or degree of action in mammalian cell types as previously described in model organisms. 23,24 Nonetheless, one study has connected Lis1/Pafah1b1, a dyneinbinding microtubulecapturing and spindle-orienting protein, with its ability to modulate murine HSPC inheritance of cell fate determinants in normal hematopoiesis and leukemia.…”
Section: Introductionmentioning
confidence: 91%